2010
DOI: 10.1093/jac/dkq286
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility of unselected uropathogenic Escherichia coli from female Dutch general practice patients: a comparison of two surveys with a 5 year interval

Abstract: Over a 5 year period, the antibiotic susceptibility of uropathogenic E. coli did not change in female patients with uncomplicated UTI in the Netherlands, but ESBL prevalence increased. With respect to the prescription of antimicrobial agents, compliance with national UTI guidelines was good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 20 publications
5
38
2
Order By: Relevance
“…The lower rates were reported in outpatients from Turkey (16,17,20). Although in Netherlands, the prevalence of ESBL-producing E. coli in outpatients is lower than our country, there was a significant increasing from 2004 (0.1%) to 2009 (1%) (18). However, China (21) and Tanzania (22) have higher rates when compared to our study.…”
Section: Escherichia Colicontrasting
confidence: 72%
See 1 more Smart Citation
“…The lower rates were reported in outpatients from Turkey (16,17,20). Although in Netherlands, the prevalence of ESBL-producing E. coli in outpatients is lower than our country, there was a significant increasing from 2004 (0.1%) to 2009 (1%) (18). However, China (21) and Tanzania (22) have higher rates when compared to our study.…”
Section: Escherichia Colicontrasting
confidence: 72%
“…Some other studies showed similar results but some found higher susceptibility rates in ESBL-producing E. coli isolates (18,21,29).…”
Section: Escherichia Colisupporting
confidence: 53%
“…With the development of resistance, commonly used antibiotics, eg, amoxicillin, cotrimoxazole, and the quinolones, are showing decreasing activity, particularly since new mechanisms of resistance have been detected in the community. [12][13][14]219 This resistance may be observed also in veterinary practice, 220 in sewage sludge and liquid pig manure, 221 and in cow excrement. 222 Given that the choice of a first-line treatment for uncomplicated urinary tract infection must be made according to the probability of success/failure, the likelihood of adverse effects, and cost considerations, fosfomycin appears to be a convenient option at the present time.…”
Section: Patient Preferencementioning
confidence: 94%
“…Far from these descriptions, fosfomycin still exhibits good antibacterial activity, [12][13][14][15][16][17] mainly because its use has been limited in therapeutics. This underutilization was probably due to early problems in determining its true in vitro activity, 15 demonstrating its efficacy as a single agent, 15,18 and the resulting lack of inclination of pharmaceutical companies to perform clinical studies of fosfomycin in combination regimens.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely to contribute to the emergence of resistant bacteria, such as extended-spectrum--lactamase (ESBL)-producing bacteria (Hasman et al 2005;Pfeifer et al 2010;Chander et al 2011;Hur et al 2011;Persoons et al 2011). Cephalosporins are assigned as critically important antimicrobials for human health (WHO 2007) and should, therefore, be used sparingly in veterinary practice to prevent the occurrence of bacterial resistance (Wittum 2007;European Medicines Agency 2009;Den Heijer et al 2010;Dutil et al 2010;Ewers et al 2010).…”
Section: Introductionmentioning
confidence: 99%